High miR156 Expression Is Required for Auxin-Induced Adventitious Root Formation via MxSPL26 Independent of PINs and ARFs in Malus xiaojinensis - Xu, Xiaozhao; Li, Xu; Hu, Xingwang; Wu, Ting; Wang, Yi; Xu, Xuefeng; Zhang, Xinzhong; Han, Zhenhai (Frontiers in Plant Science, 2017)
Abstract Adventitious root formation is essential for the vegetative propagation of perennial woody plants. During the juvenile-to-adult phase change mediated by the microRNA156 (miR156), the adventitious rooting ability decreases dramatically in many species, including apple rootstocks. However, the mechanism underlying how miR156 affects adventitious root formation is unclear. In the present study, we showed that in the presence of the synthetic auxin indole-3-butyric acid (IBA), semi-lignified leafy cuttings from juvenile phase (Mx-J) and rejuvenated (Mx-R) Malus xiaojinensis trees exhibited significantly higher expression of miR156, PIN-FORMED1 (PIN1), PIN10, and rootless concerning crown and seminal roots-like (RTCS-like) genes, thus resulting in higher adventitious rooting ability than those from adult phase (Mx-A) trees. However, the expression of SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE26 (SPL26) and some auxin response factor (ARF) gene family members were substantially higher in Mx-A than in Mx-R cuttings. The expression of NbRTCS-like but not NbPINs and NbARFs varied with miR156 expression in tobacco (Nicotiana benthamiana) plants transformed with 35S:MdMIR156a6 or 35S:MIM156 constructs. Overexpressing the miR156-resistant MxrSPL genes in tobacco confirmed the involvement of MxSPL20, MxSPL21&22 and MxSPL26 in adventitious root formation. Together, high expression of miR156 was necessary for auxin-induced adventitious root formation via MxSPL26, but independent of MxPINs and MxARFs expression in M. xiaojinensis leafy cuttings.